Julia M. Esparza, AHIP, Medical Library Association President, 2019–2020 - Philbrick, Jodi L. (J Med Libr Assoc, 2019)
In this profile of Julia M. Esparza, AHIP, Medical Library Association President, 2019–2020, she is described as a pleasure to work with, practical, and intelligent, and she adds a spark of humor to any activity. Esparza has spent the last twelve years of her career in the Health Sciences Library and Department of Medical Library Science at Louisiana State University Health Sciences Center Shreveport. She is an excellent role model for medical librarians who want to engage in scholarly activities and is active in supporting the educational needs of health care providers, students, library personnel, and the community through her instructional efforts.